The private and public insurance value of conservative biodiversity management - Stefan Baumgärtner; Martin F. Quaas (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2006)
The ecological literature suggests that biodiversity reduces the variance of ecosystem services. Thus, conservative biodiversity management has an insurance value to risk-averse users of ecosystem services. We analyze a conceptual ecological-economic model in which such management measures generate a private benefit and, via ecosystem processes at higher hierarchical levels, a positive externality on other ecosystem users. We find that ecosystem management and environmental policy depend on the extent of uncertainty and risk-aversion as follows: (i) Individual effort to improve ecosystem quality unambiguously increases. The free-rider problem may decrease or increase, depending on the characteristics of the ecosystem and its management; in particular, (ii) the size of the externality may decrease or increase, depending on how individual and aggregate management effort influence biodiversity; and (iii) the welfare loss due to free-riding may decrease or increase, depending on how biodiversity influences ecosystem service provision.
Keywords: Q57; H23; D8; D62; 330; biodiversity; ecosystem services; ecosystem management; free-riding; insurance; public good; risk-aversion; uncertainty; Biodiversität; Umweltpolitik; Trittbrettfahrerverhalten; Entscheidung bei Unsicherheit; Risikoaversion; Versicherungsprämie; Externer Effekt; Theorie